Implementation of Religious Moderation in Islamic Religious Education Learning at SMK N 1 Surakarta - Inez Yuliane; Muhtoharrun Jinan (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
The purpose of this study is to understand how the moderation programme is implemented at SMK N 1 Surakarta Indonesia through PAI learning. This research uses a descriptive research design, which analyses some secondary data which includes literature, books, journals, and scientific works related to data moderation at SMK N 1 Surakarta. The results of the study, the concept of moderation in general at SMK N 1 Surakarta can be explained through the PAI learning process. School efforts in implementing moderation programmes through the use of media, such as websites and social media, show the active involvement of students in assessing literacy products. Moderation through the use of media, such as websites or social media, shows students' active participation in evaluating literacy products.